Profiling the time-course changes in neuromuscular function and muscle damage over two consecutive tournament stages in elite rugby sevens players - West, D. J.; Cook, C. J.; Stokes, K. A.; Atkinson, P.; Drawer, S.; Bracken, R. M.; Kilduff, L. P. (Journal of Science and Medicine in Sport, 2014)
Many International Rugby Board (IRB) sevens competitions require that two tournament stages are played over consecutive weekends, but the impact this has on player physical performance and recovery is lacking. We examined the influence of two consecutive tournaments on neuromuscular function (NMF) and muscle damage in rugby sevens players. Ten elite international rugby sevens players completed this observational study over 2 tournaments, separated by 5 days, during the IRB sevens series. On the morning of day 1 and 2, of both tournament 1 (T1) and 2 (T2), players performed countermovement jumps (CMJ; jump height [JH]) and capillary blood samples (creatine kinase [CK]) were collected. After the last match of each day, further capillary samples were collected. Additional, CMJ were performed 12 and 60hr post-T1. Player JH decreased from day 1 to day 2 during T1 (mean±SD; -6.0±5.4%; P=0.016), was reduced at 12 (-26.1±5.0%; p<0.001) and 60hr post-T1 (-7.1±4.8%; P=0.003) and remained lower, at am day 1 of T2 (-8.0±6.0%; P=0.007), when compared with day 1 of TPlayer JH was lower on day 1 and 2 of T2, compared with T1 (p<0.05). CK concentrations were greater than baseline at all time points during each tournament (p<0.001); no between tournament differences in CK responses existed (P=0.302). A single sevens tournament reduces NMF such that players are not fully recovered by the start of the second competition stage, however CK returns to baseline in-between and shows the same pattern across two consecutive tournaments.